Report of the Committee on Power - Planning Commission (Planning Commission, 1980)
Electric power has proved itself to be one of the most powerful instruments of social and economic change that the world has seen. It has many unique properties. To the household consumer, it represents the most convenient and versatile form of energy providing simultaneously motive power, heat or light. In many vital industries, there is no substitute for electric power. Whereas its use in India in the past was largely confined to industrial and domestic consumers, power is today playing an increasingly important role in agriculture and transport spurred on by the rising costs of petroleum products and the growing burden they throw on the country's balance of payments. Power, being a secondary form of energy, can be produced from almost any energy source - coal, wood, petroleum, biogas, water pressure, fissible elements, wind and the sun.
Government of India Ministry of Energy Department of Power
Government of India Ministry of Energy Department of Power